Geterogenety walls of heart on stages of early human cardiogenesis. - Kozlov S.V.; Savenkova H.A. (Морфологія, 2007)
We explored dynamics of structural-functional transformations of tissue and cellular components of walls of heart during the early embryology development of man. We took the hearts served by material 10 embryos of man 6-10 weeks of prenatal development, which fixed by the liquid Buen as a research material and made cuts on the generally accepted methods. The research showed, that forming of walls of early embryonic heart has already had definite geteromorphology on the most early stages of cardiogenesis. Exposed some stages of forming of walls of heart: formation of the three-layered wall of early tubular heart; delyamination of myocardium of cardiac wall of ventricles; perforation of delyamination plate of ventricles and formation of the myocardial thrusting out in the road clearance of heart in ventricules that is formation of trabeculas; union of basal parts of trabecul; forming of the multilevel spiral system of myocardium.